Building a bicycle suitability map for Coimbra - Tralhao, Lino (2016)
The adoption of faster modes of transportation (mainly the private car) has changed profoundly the spatial organisation of cities. The increase in distance covered due to increased speed of travel and to urban sprawl leads to an increase in energy consumption, being the transportation sector a huge consumer responsible for 61.5% of total world oil consumption and a global final energy consumption of 31.6% in EU-27 (2007). Due to unsustainable transportation conditions, many cities suffer from congestion and various other traffic problems. Such situations get worse with solutions mostly seen in the development of new infrastructure for motorized modes of transportation, and construction of car parking structures. The bicycle, considered the most efficient among all modes of transportation including walking, is a travel mode that can be adopted in most cities contributing for urban sustainability given the associated environmental, economic and social advantages. In many nations a large number of policy initiatives have focused on discouraging the use of private cars, encouraging the use of sustainable modes of transportation, like public transportation and other forms such as bicycling. Given the importance of developing initiatives that favour the use of bicycle as an urban transportation mode, an analysis of city suitability, including distances and slopes of street network, is crucial in order to help decision-makers to plan the city for bicycle. In this research Geographical Information Systems (GIS) technology was used for this purpose and some results are presented concerning the city of Coimbra.